Effects of oxygen concentration variation on the structural and optical properties of reactive sputtered WOx thin film - Mahjabin S.; Mahfuzul Haque M.; Khan S.; Selvanathan V.; Jamal M.S.; Bashar M.S.; Alkhammash H.I.; Ismail Hossain M.; Shahiduzzaman M.; Amin N.; Sopian K.; Akhtaruzzaman M. (Elsevier Ltd, 2023)
Electron transport properties; Finite difference time domain method; Infrared devices; Optoelectronic devices; Oxide films; Perovskite; Perovskite solar cells; Refractive index; Scanning electron microscopy; Spectroscopy; Surface roughness; Thin films; Transition metal oxides; Transition metals; Concentration variation; Effect of oxygen; Gas flowrate; Optical parameter; Optical-; Oxygen concentrations; Property; Structural and optical properties; Thin-films; Transition-metal oxides; Oxygen; absorption; electron; film; gas flow; optical property; oxygen; perovskite; tungsten; X-ray diffraction